THE EFFECT OF INTERACTIVE MULTIMODALITY EBOOKS USING STUDENT-CENTERED LEARNING (SCL) ON NURSING STUDENTS’ LEARNING INTEREST IN THE ERA OF SOCIETY 5.0 - Sapariah Anggraini; Maria Silvana Dhawo (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2025)
Introduction: In response to the Society 5.0 era, nursing education must adapt by integrating digital-based learning approaches that emphasize Student-Centered Learning (SCL). However, many educators continue to rely on traditional Teacher-Centered Learning (TCL) methods, where students passively receive information, often resulting in disengagement and boredom. To address this challenge, an interactive multimodality eBook was developed to support digital teaching practices and enhance student learning interest. This study aimed to analyze the effect of providing interactive multimodality eBooks using the SCL method on nursing students’ learning interest in the Society 5.0 era.Methods: This quasi-experimental study used a post-test control group design. The sample consisted of 58 fourth-semester nursing students selected through total sampling. The intervention group received the interactive multimodality eBook integrated with SCL, while the control group followed conventional learning methods. Student learning interest was measured using a validated questionnaire. Data were analyzed using an independent sample t-test with a significance level of 0.05.Results: There was a significant difference in learning interest between the two groups. The intervention group had a mean score of 19.66, classified as high, while the control group had a mean score of 13.77, classified as moderate. The p-value was 0.001 (p < 0.05), and the 95% confidence interval ranged from 3.513 to 6.261. These results indicate a significant effect of the interactive multimodality eBook using the SCL method on increasing students’ learning interest.Conclusion: Interactive multimodality eBooks can be effectively integrated into nursing education to promote digital literacy, foster independent learning, and enhance student engagement. Their use aligns with the goals of Society 5.0 by combining technology and education to create a more adaptive and student-focused learning environment.